Cardiopulmonary Lesions in Sheep Produced by Experimental Acute Clostridium Perfringens Type D Enterotoxemia. Issue 1 (January 2021) - Giannitti, Federico; García, Jorge P.; Rood, Julian I.; Adams, Vicki; Armendano, Joaquín I.; Beingesser, Juliann; Uzal, Francisco A.
Enterotoxemia caused by Clostridium perfringens type D is one of the most prevalent clostridial diseases of sheep. The lesions of the acute form of this disease, particularly the cerebral lesions, are well characterized; however, detailed descriptions of the cardiac and pulmonary lesions are lacking. Here we describe cardiopulmonary lesions in experimental acute type D enterotoxemia in sheep and determine the role of epsilon toxin (ETX) in the development of these lesions. Four groups of 6 sheep were intraduodenally inoculated with either a wild-type C. perfringens type D strain; its etx knockout mutant, which is unable to produce ETX; the etx mutant complemented with the wild-type etx gene, which regains the ETX toxigenic ability; or sterile culture medium as a control. All sheep were subjected to postmortem examination within 24 hours of inoculation. Lesion scores were compared between groups for pulmonary edema; hydrothorax; ascites; hydropericardium; endocardial, myocardial and epicardial hemorrhages; microscopic lesions of acute myocardial degeneration and necrosis; and myocardial, endocardial, and epicardial edema, hemorrhage, and inflammation. Only sheep inoculated with the wild-type and complemented ETX-toxigenic bacterial strains developed cardiopulmonary lesions, which were present in varying degrees of severity and proportions. These lesions were not present in sheep inoculated with the etx mutant or in the negative control. We conclude that severe acute cardiopulmonary lesions in sheep with experimental enterotoxemia are associated with the capacity of the strains to produce ETX. These changes are likely contributors to the clinical signs and even death of affected animals.